Numerical simulation on dust removal mechanism of magnetoelectric droplets and collision wetting coal dust - Guangting XIONG; Shaocheng GE; Liying SUN; Xingyu PANG; Shuo LIU; Xi CHEN; Jun NIAN (Meitan xuebao, 2023)
In order to further improve the atomization and wetting performance of droplets, and increase the control efficiency of fine dust, in this study, the non-wetting anthracite dust in the Jincheng Mine was taken as an example. The method of the combination of the crossover experiments about magnetoelectric property coupled by surface tension, the two-phase flow numerical simulation on spherical droplet-dust particle collision by Comsol and the experiment of dust-reduction efficiency comparison was adopted. By applying the kinetic characteristics of spherical droplet-dust collision to spray dust reduction, the kinetic behaviors of magnetized and charged droplets capturing coal dust particles were investigated, and the dust suppression mechanism of magneto-electric coupled water mist was revealed. The results show that there is no linear positive correlation between magnetisation strength and droplet surface tension. The relationship between magnetisation, charge and magneto-electric coupling ability to improve droplet wettability is as follows: magneto-electric coupling>charge>magnetisation. For magnetoelectric spray, there exist optimum coupling parameters. When the magnetization intensity is 300 MT and the charge voltage is 8 kV, the surface tension of the droplet is the minimum (9.20 mN/m). In the process of collision between spherical droplets and coal dust particles, magneto-electric coupling eliminates the adverse effects of changes in relative collision velocity and particle-size-ratio on that droplets capture coal dust particles. At this time, the magnetoelectric droplets will not rebound on the surface of the coal dust particles. Compared with the normal droplets, the magnetoelectric droplets are more likely to split and produce satellite droplets. Therefore, the atomization performance is improved, the concentration of fine droplets is increased and the probability of the collision between droplets and coal dust particles is increased. Moreover, the surface tension and viscosity of the magnetoelectric droplets are reduced, and the spreading range on the surface of coal dust particles is expanded by 44.98%, which improves the atomization and wetting performance of droplets. By comparing the dust reduction effect of magnetoelectric water mist with ordinary water mist, it was found that the reduction efficiency of the full dust and the respirable dust for magneto-electric water mist reached 94.07% and 82.69% respectively, which increased by 39.16% and 42.29% respectively.